The Influence of Mobile Legends Online Gaming Intensity on Learning Motivation among Junior High School Students - Bustamam, Nurbaity; Erna Shafera; Dara Rosita (IKIP Siliwangi, 2025)
This study aims to examine the effect of online gaming intensity, specifically Mobile Legends, on the learning motivation of junior high school students in Lamno, Aceh Jaya Regency. The research employed a descriptive quantitative approach with an ex post facto design, involving 133 students from three junior high schools selected using total sampling. The instruments used were an online gaming intensity scale and a learning motivation scale, with data analyzed using simple linear regression. The results showed that 53% of students fell into the moderate category for online gaming intensity. Meanwhile, 74% of students had high learning motivation. Regression analysis revealed that the influence of online gaming intensity on learning motivation was very small, accounting for only 1%. The conclusion indicates that the intensity of playing online games does not significantly affect students’ learning motivation. The implication of this study serves as a reference for educators, parents, and school counselors to understand better the impact of online gaming, specifically Mobile Legends, on students’ learning motivation and to develop balanced strategies for managing gaming habits and academic engagement.